A composite material, its preparation and use
Patent Information
- Application Number
- CN202410285129.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-13
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2044-03-13
AI Technical Summary
[0003]针对普通表面处理技术制备的单层涂层,虽能制备粉末颗粒均匀的涂层,但厚度薄,各方面性能有待进一步提升
[0033](1)本发明的制备方法方法制得的块体金属基复合材料,能够使增强相更加均匀分布,在温度场(感应加热)和力场(超声振动)作用下,基体能发生动态再结晶,增强颗粒能进一步细化,从而更好的提高综合性能。
Smart Images

Figure CN118048627B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of metal matrix composite material processing technology, and in particular to a composite material, its preparation method and application, specifically to a bulk metal matrix composite material, its preparation method and application. Background Technology
[0002] There is a strong market demand for high-strength metal matrix composites in various fields such as biomedicine, lightweight manufacturing, and aerospace. Currently, metal alloys, such as magnesium-based alloys, titanium-based alloys, and aluminum-based alloys, have seen some applications. However, metal alloys typically have limited properties and cannot meet the complex and multi-functional requirements of various applications, severely restricting their development and application. Preparing composite materials by combining an alloy matrix with reinforcing phases, wear-resistant phases, and corrosion-resistant phases can effectively improve the comprehensive mechanical properties, wear resistance, corrosion resistance, and other properties of metal matrix materials. Metal matrix composites utilize surface treatment technology to achieve metallurgical bonding between two or more metals or non-metals with different physical, chemical, and mechanical properties, resulting in new materials where the metal matrix retains its original characteristics. However, due to the addition of reinforcing, wear-resistant, and corrosion-resistant phases, the overall physical, chemical, and mechanical properties of the composite material are significantly improved compared to pure metals or alloys.
[0003] While single-layer coatings prepared using conventional surface treatment techniques can produce coatings with uniform powder particles, they are thin and their performance in various aspects needs further improvement.
[0004] In view of this, the present invention is proposed. Summary of the Invention
[0005] The purpose of this invention is to provide a composite material, its preparation method, and its application. The bulk metal matrix composite material prepared by this method has excellent tensile strength and elongation properties and can be applied to different fields according to requirements.
[0006] A first aspect of the present invention provides a method for preparing a composite material, comprising the following steps:
[0007] S1. Through surface treatment technology, in an inert gas atmosphere, reinforcing particles are combined with a metal matrix to form a particle-reinforced metal matrix composite coating.
[0008] S2. Cut several portions of particle-reinforced metal matrix composite coating, stack them in multiple layers along the coating thickness direction, and then fix and clamp them to form a coating group.
[0009] S3. Induction heating is applied to the coating assembly;
[0010] S4. When the temperature of the coating group reaches 100-400°C below the melting point of the substrate, ultrasonic vibration compression is applied to the coating group to obtain the composite material.
[0011] This invention controls the uniform distribution of reinforcing particles in a metal matrix through surface treatment technology, forming a particle-reinforced metal matrix composite coating. By applying a temperature field (induction heating) and a force field (ultrasonic vibration) to multiple composite coatings, a bulk composite material of a certain size is prepared. The reinforcing phase can be uniformly distributed, and the matrix can undergo dynamic recrystallization under the action of the temperature and force fields, and the reinforcing particles can be further refined, thereby improving the comprehensive performance of the composite material.
[0012] Preferably, the following steps are included before step S1:
[0013] S0. The surface of the metal substrate is sanded with sandpaper to remove surface oxides and obtain a clean surface, then rinsed in ethanol and dried.
[0014] Preferably, in step S1, the surface treatment technology includes one or more of the following: laser casting, laser cladding, and thermal spraying.
[0015] Preferably, the laser cladding method includes one or more of the following: laser cladding pre-powder method and laser cladding synchronous powder feeding method.
[0016] Preferably, step S1 is repeated multiple times to obtain several portions of particle-reinforced metal matrix composite coating.
[0017] Preferably, the thickness of the particle-reinforced metal matrix composite coating is 0.5 mm to 5 mm.
[0018] Preferably, in step S1, the reinforcing particles are dried.
[0019] Preferably, in step S1, the mass ratio of the reinforcing particles to the metal matrix (containing impurities) is (5-50):(50-95); more preferably, it is (10-30):(70-90).
[0020] Preferably, in step S1, the reinforcing particles include one or more of metal powder and ceramic powder; more preferably, the metal powder is Ti particles.
[0021] In one specific embodiment, the Ti particles are spherical Ti particles with a diameter of 40 to 100 μm and an average particle size of 75 μm.
[0022] Preferably, in step S1, the metal matrix includes one or more of magnesium and magnesium alloys.
[0023] In one specific embodiment, the metal substrate is an AZ31 magnesium plate with a melting point of 650°C, a thickness of 5mm, and dimensions of 5mm*50mm*100mm.
[0024] Preferably, in step S1, the inert gas is argon or nitrogen.
[0025] In one specific embodiment, in step S2, the particle-reinforced metal matrix composite coating consists of 5 parts.
[0026] Preferably, in step S4, when the temperature of the coating group reaches 350-450°C below the melting point of the substrate, ultrasonic vibration compression is applied to the coating group.
[0027] Preferably, in step S4, the vibration frequency of the ultrasonic vibration compression is 10KHz to 40KHz, more preferably 10KHz to 20KHz; and the applied load intensity is 10MPa to 50MPa, more preferably 10MPa to 20MPa.
[0028] Preferably, in step S4, one or more of the following methods are adopted, such as constant temperature and pressure, variable temperature and pressure, constant temperature and pressure, or variable temperature and pressure, depending on the thickness of the stacked sample, the number of combined coating layers, the hardness of a single coating layer, and the expected performance of the bulk composite material.
[0029] In one specific embodiment, when the coating group reaches 200℃~300℃, ultrasonic vibration compression with a load of 10MPa~20MPa at a frequency of 10KHz~20KHz is applied to the coating group, and the temperature and pressure are maintained for 10min to obtain Mg-Ti composite material.
[0030] In a second aspect, the present invention provides a composite material prepared by the above-described preparation method.
[0031] A third aspect of the present invention provides applications of the above-mentioned composite material in the fields of biomedicine, lightweight manufacturing, and aerospace.
[0032] The present invention has the following beneficial effects:
[0033] (1) The bulk metal matrix composite material prepared by the preparation method of the present invention can make the reinforcing phase more uniformly distributed. Under the action of temperature field (induction heating) and force field (ultrasonic vibration), the matrix can undergo dynamic recrystallization and the reinforcing particles can be further refined, thereby improving the overall performance.
[0034] (2) The preparation method of the present invention has low equipment requirements, simple preparation process, low production cost, and is easy to realize large-scale industrial production.
[0035] (3) The preparation method of the present invention can obtain alloys with different mechanical properties by controlling the process parameters of induction heating and ultrasonic vibration, so as to meet the needs of different fields. Attached Figure Description
[0036] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.
[0037] Figure 1 This is a SEM image of the fracture surface of the Mg-Ti composite material prepared in Example 1 of the present invention.
[0038] Figure 2 The metallographic structure of the Mg-Ti composite material prepared in Example 1 of this invention is shown. Detailed Implementation
[0039] It should be noted that the following detailed descriptions are illustrative and intended to provide further explanation of this application. Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains.
[0040] It should be noted that the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the exemplary embodiments according to this application. As used herein, the singular form includes the plural form unless the context clearly indicates otherwise. Furthermore, it should be understood that when the terms "comprising" and / or "including" are used in this specification, they indicate the presence of features, steps, operations, devices, components, and / or combinations thereof.
[0041] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0042] Example 1
[0043] This embodiment provides a method for preparing a composite material, using raw materials including:
[0044] Metal substrate: 5mm thick AZ31 magnesium plate (magnesium alloy), with dimensions of 5mm*50mm*100mm;
[0045] Reinforcing particles: Spherical Ti particles with a diameter of 40–100 μm and an average particle size of 75 μm.
[0046] The specific preparation process is as follows:
[0047] S0. Before laser treatment, the magnesium alloy surface is polished with 800-grit silicon carbide sandpaper to remove surface oxides and obtain a clean surface. Then it is rinsed in ethanol and finally dried in air.
[0048] S1. After drying the Ti particles, a Ti particle-reinforced magnesium-based composite coating is formed on the surface of the magnesium alloy substrate by laser cladding technology under an atmosphere of argon as a protective gas.
[0049] Repeat step S1 to obtain 5 Ti particle-reinforced magnesium-based composite coatings.
[0050] S2. Cut off 5 portions of Ti particle-reinforced magnesium-based composite coating, stack the 5 coatings along their thickness direction, and fix the coating group in place.
[0051] S3. Induction heating is applied to the coating assembly.
[0052] S4. When the coating group reaches 200℃, apply ultrasonic vibration compression with a load of 10MPa at a frequency of 20KHz to the coating group, and keep it at the temperature and pressure for 10min to obtain the Mg-Ti composite material.
[0053] The fracture surface SEM of the Mg-Ti composite material prepared in this embodiment is shown in [Figure 1]. Figure 1 As can be seen from the figure, after induction heating and ultrasonic vibration compression treatment, the fracture surface of the Mg-Ti composite material is cleavage fracture, and there are a large number of cleavage steps on the fracture surface.
[0054] The metallographic structure of the Mg-Ti composite material prepared in this embodiment is shown in the figure. Figure 2 As can be seen from the figure, the microstructure of the Mg-Ti composite material is significantly refined after induction heating and ultrasonic vibration compression treatment.
[0055] Example 2
[0056] This embodiment is basically the same as embodiment 1, except that: S4, when the coating group reaches 200°C, ultrasonic vibration compression with a frequency of 20KHz and a load of 20MPa is applied to the coating group, and the temperature and pressure are maintained for 10 minutes to obtain the Mg-Ti composite material.
[0057] The fracture surface SEM and metallographic structure results of the Mg-Ti composite material prepared in this embodiment are basically consistent with those in Example 1.
[0058] Example 3
[0059] This embodiment is basically the same as embodiment 1, except that: S4, when the coating group reaches 300°C, ultrasonic vibration compression with a frequency of 20KHz and a load of 10MPa is applied to the coating group, and the temperature and pressure are maintained for 10 minutes to obtain the Mg-Ti composite material.
[0060] The fracture surface SEM and metallographic structure results of the Mg-Ti composite material prepared in this embodiment are basically consistent with those in Example 1.
[0061] Example 4
[0062] This embodiment is basically the same as embodiment 1, except that: S4, when the coating group reaches 300°C, ultrasonic vibration compression with a frequency of 20KHz and a load of 20MPa is applied to the coating group, and the temperature and pressure are maintained for 10 minutes to obtain Mg-Ti composite material.
[0063] The fracture surface SEM and metallographic structure results of the Mg-Ti composite material prepared in this embodiment are basically consistent with those in Example 1.
[0064] Comparative Example 1
[0065] This comparative example provides a method for preparing a composite material, using raw materials including:
[0066] Metal substrate: 5mm thick AZ31 magnesium plate (magnesium alloy), with dimensions of 5mm*50mm*100mm;
[0067] Reinforcing particles: Spherical Ti particles with a diameter of 40–100 μm and an average particle size of 75 μm.
[0068] The specific preparation process is as follows:
[0069] S0. Before laser treatment, the magnesium alloy surface is polished with 800-grit silicon carbide sandpaper to remove surface oxides and obtain a clean surface. Then it is rinsed in ethanol and finally dried in air.
[0070] S1. After drying the Ti particles, a Ti particle-reinforced magnesium-based composite coating is formed on the surface of the magnesium alloy substrate by laser cladding technology under an atmosphere of argon as a protective gas.
[0071] Repeat step S1 to obtain 5 Ti particle-reinforced magnesium-based composite coatings.
[0072] S2. Cut off 5 portions of Ti particle-reinforced magnesium-based composite coating, stack the 5 coatings along their thickness direction, and fix the coating assembly in place.
[0073] S3. Apply ultrasonic vibration compression with a frequency of 20KHz and a load of 10MPa to the coating group and hold the pressure for 10min to obtain the Mg-Ti composite material.
[0074] Comparative Example 2
[0075] This comparative example is basically the same as Comparative Example 1, except that:
[0076] S3. Apply ultrasonic vibration compression with a frequency of 20KHz and a load of 20MPa to the coating group and hold the pressure for 10min to obtain the Mg-Ti composite material.
[0077] Comparative Example 3
[0078] This comparative example provides a method for preparing a composite material, using raw materials including:
[0079] Metal substrate: 5mm thick AZ31 magnesium plate (magnesium alloy), with dimensions of 5mm*50mm*100mm;
[0080] Reinforcing particles: Spherical Ti particles with a diameter of 40–100 μm and an average particle size of 75 μm.
[0081] The specific preparation process is as follows:
[0082] S0. Before laser treatment, the magnesium alloy surface is polished with 800-grit silicon carbide sandpaper to remove surface oxides and obtain a clean surface. Then it is rinsed in ethanol and finally dried in air.
[0083] S1. After drying the Ti particles, a Ti particle-reinforced magnesium-based composite coating is formed on the surface of the magnesium alloy substrate by laser cladding technology under an atmosphere of argon as a protective gas.
[0084] Repeat step S1 to obtain 5 Ti particle-reinforced magnesium-based composite coatings.
[0085] S2. Cut off 5 portions of Ti particle-reinforced magnesium-based composite coating, stack the 5 coatings along their thickness direction, and fix the coating assembly in place.
[0086] S3. Heat the rolling mill rolls to 200°C and roll the coating group to obtain Mg-Ti composite material.
[0087] Comparative Example 4
[0088] This comparative example is basically the same as Comparative Example 3, except that:
[0089] S3. Heat the rolling mill rolls to 300°C and roll the coating group to obtain Mg-Ti composite material.
[0090] Test case
[0091] The tensile strength and elongation of the composite materials prepared in Examples 1-4 and Comparative Examples 1-4 were tested, and the test results are shown in Table 1.
[0092] Table 1
[0093]
[0094] As can be seen from the results in Table 1, the composite materials prepared by Examples 1-4 using the "surface treatment technology + induction heating + ultrasonic vibration" method of the present invention are superior to the composite materials prepared by Comparative Examples 1-4 in terms of tensile strength and elongation.
[0095] In summary, the method of this invention for preparing bulk metal matrix composites enables a more uniform distribution of the reinforcing phase. Under the influence of a temperature field (induction heating) and a force field (ultrasonic vibration), the matrix can undergo dynamic recrystallization, and the reinforcing particles can be further refined, thereby improving the overall performance. The preparation method of this invention has low equipment requirements, a simple preparation process, low production costs, and is easy to scale up for industrial production. Furthermore, by controlling the process parameters of ultrasonic vibration and induction heating, the preparation method of this invention can obtain alloys with different mechanical properties to meet the needs of different fields.
[0096] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a composite material, characterized in that, Includes the following steps: S1. Through surface treatment technology, in an inert gas atmosphere, reinforcing particles are combined with a metal matrix to form a particle-reinforced metal matrix composite coating. S2. Cut several portions of particle-reinforced metal matrix composite coating, stack them in multiple layers along the coating thickness direction, and then fix and clamp them to form a coating group. S3. Induction heating is applied to the coating assembly; S4. When the temperature of the coating group reaches 100~400℃ below the melting point of the substrate, ultrasonic vibration compression is applied to the coating group. The vibration frequency of the ultrasonic vibration compression is 10kHz~40kHz, and the applied load intensity is 10MPa~50MPa, to obtain the composite material.
2. The method for preparing the composite material according to claim 1, characterized in that, In step S1, the surface treatment technology includes one or more of the following: laser casting, laser cladding, and thermal spraying.
3. The method for preparing the composite material according to claim 1, characterized in that, In step S1, the mass ratio of the reinforcing particles to the metal matrix is (5-50):(50-95).
4. The method for preparing the composite material according to claim 1, characterized in that, In step S1, the reinforcing particles include one or more of metal powder and ceramic powder.
5. The method for preparing the composite material according to claim 4, characterized in that, The metal powder is Ti particles.
6. The method for preparing the composite material according to claim 1, characterized in that, In step S1, the metal matrix includes one or more of magnesium and magnesium alloys.
7. The method for preparing the composite material according to claim 1, characterized in that, In step S1, the inert gas is argon or nitrogen.
8. A composite material, characterized in that, It is prepared by the preparation method according to any one of claims 1-7.
9. The application of the composite material according to claim 8 in the fields of biomedicine, lightweight manufacturing, and aerospace.
Citation Information
Patent Citations
Method for preparing lithium-magnesium-based composite material by reciprocating extrusion
CN101967568A
High-modulus magnesium alloy and rapid preparation method and application thereof
CN116083826A